1985
DOI: 10.1002/art.1780280208
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenetic studies of juvenile dermatomyositis. III. Study of antibody to organ‐specific and nuclear antigens

Abstract: Ninety children with definite juvenile dermatomyositis (JDMS), who had been HLA typed, were tested for the presence of tissue or organ‐specific antibodies. Sixty had active disease at the time of study. The mean disease duration was 4 years, and 30 had soft tissue calcifications. The following autoantibodies were sought: thyroid, gastric parietal cells, smooth muscle, striated muscle, microsomes, mitochondria, DNA, extractable nuclear antigen, Sm, PM‐1, antinuclear antibody (ANA), and rheumatoid factor. Only t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
1

Year Published

1986
1986
2013
2013

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…In addition to the increase in B cells, over 70% of active untreated JDM patients have a positive anti-nuclear antibody test and selected (not polyclonal) elevation in Ig levels (22,24). The peripheral lymphopenia and the relative increase in the percentage of B lymphocytes may be associated with a decrease in circulating CD8 ϩ cells, with increased localization of CD8 ϩ lymphocytes in the affected muscle (23); however, intrinsic B-cell activation has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increase in B cells, over 70% of active untreated JDM patients have a positive anti-nuclear antibody test and selected (not polyclonal) elevation in Ig levels (22,24). The peripheral lymphopenia and the relative increase in the percentage of B lymphocytes may be associated with a decrease in circulating CD8 ϩ cells, with increased localization of CD8 ϩ lymphocytes in the affected muscle (23); however, intrinsic B-cell activation has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The study population consisted of 12 children with definite JDM (as defined above), who had been observed in the rheumatology clinic of Children's Memorial Hospital, Chicago (17)(18)(19)(20)(21)(22)(23). These children, whose ages ranged from 3-11 years (mean 7.0), had been extensively evaluated (17)(18)(19)(20)(21)(22)(23). They were not admitted to this phase of the study unless their date of disease onset was sharply identified and unless peripheral blood samples had been obtained within 4 months of disease onset, and promptly separated and kept frozen at -70°C for serologic investigations.…”
Section: Methodsmentioning
confidence: 99%
“…These observations suggested that coxsackie B viruses might be involved in the pathogenesis of JDM. To assess this possibility, we tested for antibodies to coxsackie B and other implicated viruses in serum samples from an extensively studied group of children with definite JDM (17)(18)(19)(20)(21)(22)(23) and from 2 groups of controls.…”
mentioning
confidence: 99%
“…The expression profiles do not distinguish between an active infection in the biopsy and a hit-and-run mechanism in which an infection initiates a cascade that persists after the active organism has been cleared. Genes involved in Ag presentation may hold clues to this issue, because the majority of JDM patients have consistent evidence of a very limited spectrum of autoantibodies (11)(12)(13). Genes controlling the early phase of Ag presentation were up-regulated in JDM; they include MHC class II proteosome elements LMP2 (6-fold higher) and LMP7 (ϳ42-fold higher) and Ag transporter TAP1 (also called RING4, up ϳ37-fold), which presents Ags to CD8 ϩ T cells (common in JDM muscle).…”
Section: Antiviral Cascades In the Vasculature And Infiltrating Immunmentioning
confidence: 99%
“…For example, Ig is deposited on muscle fibers in association with the membrane attack complex (10). Although a majority of JDM sera contain a speckled pattern antinuclear Ab of unknown specificity (11), and a subset of these sera have Ab to a 56-kDa nuclear protein (12), which is more frequent in DQA1*0501-positive children with JDM (13), Ab-dependent cell-mediated cytotoxicity has not been demonstrated (14). Peripheral blood from untreated JDM demonstrates a lymphopenia, with a selective decrease in the CD8 ϩ subset as well as ICAM-I-positive non-CD19 ϩ cells (presumed T cells) (15).…”
mentioning
confidence: 99%